Efektivitas GAKKUMDU dalam Penegakan Hukum Pemilu 2024 di Karanganyar: Evaluasi dan Tantangan - Feri Budi Lestanto (Jurnal Hukum Lex Generalis, 2025)
violations in Karanganyar. Using a qualitative approach and in-depth interviews, it finds good inter-agency coordination but highlights issues in legal substance, institutional structure, and legal culture. Limited authority and sectoral egos hinder performance. Regulatory reform is needed to enable Gakkumdu to play a more substantive role in electoral law enforcement.